2023
DOI: 10.3897/zookeys.1138.95626
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mitogenomics and phylogenetic analyses of the genus Menida (Hemiptera, Heteroptera, Pentatomidae)

Abstract: In order to explore the genetic diversity and phylogenetic relationship of the genus Menida Motschulsky, 1861 and reveal the molecular evolution of the family Pentatomidae, subfamily Pentatominae, complete mitochondrial genomes of three species of Menida were sequenced, and the phylogenetic relationships of tribes within the subfamily Pentatominae were studied based on these results. The mitochondrial genomes of Menida musiva (Jakovlev, 1876), M. lata Yang, 1934, and M. metallica Hsiao & Cheng, 1977 were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…typica was the first species to differentiate from Pentatomidae. These same results were obtained by Lian et al (2022) [ 66 ] and Ding et al (2023) [ 65 ]. Our study results rejected the monophyly of Pentatominae and Podopinae, and supported Asopinae as monophyletic.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…typica was the first species to differentiate from Pentatomidae. These same results were obtained by Lian et al (2022) [ 66 ] and Ding et al (2023) [ 65 ]. Our study results rejected the monophyly of Pentatominae and Podopinae, and supported Asopinae as monophyletic.…”
Section: Discussionsupporting
confidence: 88%
“…indica using second-generation sequencing technology. The arrangement of the 37 genes was consistent with that of published Pentatomidae species [ 52 , 53 , 65 ], indicating that no gene rearrangements have occurred. The nucleotide composition of the mitochondrial genome of M .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, AT (positive) and GC (negative) skews resemble the patterns normally reported for insects 29 , 91 – 93 . The length of concatenated PCGs of D. melacanthus (10,533 bp) was close to that of D. furcatus (10,351 bp), corresponding to approximately 61 and 67% of their mitogenomes, similarly to various Pentatomidae 14 , 29 , 70 , 82 , 94 . Nine PCGs ( nad2, cox1, cox2, atp8, atp6, cox3, nad3, nad6, cytb ) are encoded on the main strand and four on the complementary strand ( nad5, nad4, nad4L, nad1 ) (Fig.…”
Section: Resultsmentioning
confidence: 67%